Relativistic DFT Calculations of Hyperfine Coupling Constants in 5d Hexafluorido Complexes: [ReF(6)](2−) and [IrF(6)](2−) - Haase, Pi A. B. (John Wiley and Sons Inc., 2017)

(untitled) (Chemistry)
The performance of relativistic density functional theory (DFT) methods has been investigated for the calculation of the recently measured hyperfine coupling constants of hexafluorido complexes [ReF(6)](2−) and [IrF(6)](2−). Three relativistic methods were employed at the DFT level of theory: the 2‐component zeroth‐order regular approximation (ZORA) method, in which the spin–orbit coupling was treated either variationally (EV ZORA) or as a perturbation (LR ZORA), and the 4‐component Dirac–Kohn–Sham (DKS) method. The dependence of the results on the basis set and the choice of exchange‐correlation functional was studied. Furthermore, the effect of varying the amount of Hartree–Fock exchange in the hybrid functionals was investigated. The LR ZORA and DKS methods combined with DFT led to very similar deviations (about 20 %) from the experimental values for the coupling constant of complex [ReF(6)](2−) by using hybrid functionals. However, none of the methods were able to reproduce the large anisotropy of the hyperfine coupling tensor of complex [ReF(6)](2−). For [IrF(6)](2−), the EV ZORA and DKS methods reproduced the experimental tensor components with deviations of ≈10 and ≈5 % for the hybrid functionals, whereas the LR ZORA method predicted the coupling constant to be around one order of magnitude too large owing to the combination of large spin–orbit coupling and very low excitation energies.